Review of amphipods of the Melita group (Amphipoda: Melitidae) from the coastal waters of Sakhalin Island (Far East of Russia). III. Genera Abludomelita Karaman, 1981 and Melita Leach, 1814 - Labay, Vjacheslav S. (Zootaxa, 2016)
The taxonomic analysis of Melita group is performed. The revision of the genus Melita Leach, 1814 was held on the basis of analysis of morphological characters. Cladistic analysis of morphological relationships within genera Abludomelita and Melita is performed. Status of the genus Paraniphargus Tattersall, 1925 restored. New genera Barnardomelita gen. nov. and Ledoyeromelita gen. nov. are described and removed from the composition of the genus Melita. A review of Melita group (fam. Melitidae) from the shelf of Sakhalin Island based on all literature and own data is provided. Based on new material, two new species of the genus Abludomelita Karaman, 1981 are described: A. klitinii sp. nov. and A. okhotensis sp. nov. from the shelf of Sakhalin Island. Megamoera aequidentatum Labay, 2013 is transferred to the genus Abludomelita as A. rotundactyla (Ren, 2012) on the basis of additional morphological description of male. The new subspecies Melita shimizui sakhalinensis ssp. nov. is described from estuaries of Sakhalin Island. The keys to the world species of genera Abludomelita and Melita are provided.